The impact of hot nights on dengue incidence: a nationwide case crossover study in Brazil - Mintao Su; Junjun Chen; Zhisheng Liang; Qinfeng Zhou; Junxiong Ma; Huining Yang; Shaym Biswal; Murugappan Ramanathan; Haojun Fan; Fan Dai; Wei Huang; Minghui Ren; et al. (Infectious Diseases of Poverty)
Abstract Background Dengue fever, a mosquito-borne disease, is influenced by temperature. As global warming intensifies, the frequency of hot nights has increased. However, the relationship between hot nights and dengue transmission remains unclear. This study aimed to evaluate the impact of hot night exposures on dengue incidence. Methods We collected individual dengue data from Brazil's SINAN database (2014–2021), covering 5,708,691 patients. Hot night exposures, including the average maximum nighttime temperatures, hot night excess, and hot night duration, were calculated using the ERA5-land dataset. A case-crossover design was employed to assess the association between each hot night exposure and dengue incidence using conditional logistic regression. Results The average maximum nighttime temperature, hot night excess, and hot night duration were all significantly associated with increased risk of dengue, with odds ratios (ORs) of 1.86 (95% CI 1.86–1.87), 1.01 (95% CI 1.01–1.01), and 1.05 (95% CI 1.05–1.05), respectively. The attributable risks for each hot night exposure were 14.02% (95% CI 13.49%–14.60%), 27.80% (95% CI 27.33%–28.21%), and 26.95% (95% CI 26.58%–27.38%), respectively, when the exposure value was above the 90th percentile of its distribution. Conclusions Hot night exposures were associated with an increased risk of dengue in Brazil. The public health burden of dengue is likely to rise with increasing hot night exposures, especially as hot nights become more frequent worldwide. Implementation of targeted vector control strategies and improved access to cooling equipment, such as air-conditioning, may serve as important mitigation measures. Graphical Abstract